Cigarette Smoking-Induced Cardiac Hypertrophy, Vascular Inflammation and Injury are Attenuated by Antioxidant Supplementation in An Animal Model - Moustafa Al Hariri; Kazem Zibara; Kazem Zibara; Wissam Farhat; Yasmine Hashem; Nadia Soudani; Nadia Soudani; Farah Al Ibrahim; Eva Hamadeh; Eva Hamadeh; Asad Zeidan; Ahmad Husari; et al. (Frontiers Media S.A., 2016)
BackgroundCardiovascular diseases are the leading causes of morbidity and mortality worldwide. Cigarette smoking remains a global health epidemic with associated detrimental effects on the cardiovascular system. In this work, we investigated the effects of cigarette smoke exposure on cardiovascular system in an animal model. The study then evaluated the effects of antioxidants (AO), represented by pomegranate juice, on cigarette smoke induced cardiovascular injury. This study aims at evaluating the effect of pomegranate juice supplementation on the cardiovascular system of an experimental rat model of smoke exposure.Methods Adult rats were divided into four different groups: Control, Cigarette smoking (CS), AO, and CS + AO. Cigarette smoke exposure was for 4 weeks (5 days of exposure/week) and AO group received pomegranate juice while other groups received placebo. Assessment of cardiovascular injury was documented by assessing different parameters of cardiovascular injury mediators including: 1) cardiac hypertrophy, 2) oxidative stress (OS), 3) expression of inflammatory markers, 3) expression of Bradykinin receptor 1 (Bdkrb1), Bradykinin receptor 2 (Bdkrb2), and 4) altered expression expression of fibrotic/atherogenic markers [(Fibronectin (Fn1) and leptin receptor (ObR)].ResultsData from this work demonstrated that cigarette smoke exposure induced cardiac hypertrophy, which was reduced upon administration of pomegranate in CS + AO group. Cigarette smoke exposure was associated with elevation in oxidative stress, significant increase in the expression of IL-1β, TNFα, Fn1 and ObR in rat's aorta. In addition, an increase in aortic calcification was observed after one month of Cigarette smoke exposure. Furthermore, Cigarette smoke induced a significant up regulation in Bdkrb1 and Bdkrb2 expression levels. Finally, pomegranate supplementation exhibited cardiovascular protection assessed by the above findings and partly contributed to ameliorating cardiac hypertrophy in cigarette smoke exposed animals.Conclusion Findings from this work showed that cigarette smoking exposure is associated with significant cardiovascular pathology such as cardiac hypertrophy, inflammation, pro-fibrotic and atherogenic markers and aortic calcification in an animal model as assessed 1 month post exposure. Antioxidant supplementation prevented cardiac hypertrophy and attenuated indicators of atherosclerosis markers associated with cigarette smoke exposure.Key words: Cigarette smoking, pomegranate Juice, inflammation, hypertrophy, calcification, reactive oxygen species, cardiovascular diseases.